Cyber Warfare Antara Armenia-Azerbaijan 2020: Komparasi Strategi Media Sebagai Medan Perang Strategis - Maghfirotul Abidah (PT PUSTAKA CENDEKIA GROUP, 2024)
The war over territory between Armenia and Azerbaijan, which has been going on for a long time with the use of the military and allies in its strategy, is now increasingly complex by placing the media as an important role in the digital world era, especially in the re-emergence of the war between the two countries in 2020. Narratives have been used since 1990s, but in 2020 the level of complexity is getting higher. The media as one of the cyber war strategies acts as a strategic field for information battles between the two countries by competing to attract public sympathizers through narratives that describe the justification for their actions. Differences in regulations regarding freedom of information give rise to significant strategic differences between Armenia and Azerbaijan, which is the focus of this paper which will form a comparison. In analyzing the phenomenon of different strategic media in cyber warfare, researchers used qualitative descriptive methods with data documentation collection techniques by reading data in classical Realism theory and then presenting the results in research results. In this article, a comparison will be presented that researchers found through data that has been carried out through a triangulation process